Commentary on theOrganization ScienceSpecial Issue on Complexity - Cohen, Michael (Organization Science, 1999)
The appearance of this special issue of Organization Science reflects—and will surely increase—the attention organizational researchers are paying to studies of “complex systems.” There has been a remarkable wave of interest in this synthesis of concepts arising from the intersection of biology, physics, and computer science. However, if this line of work is to develop into a permanent source of valuable ideas for organizational researchers, rather than to prove a passing fancy, we need to begin sharpening our appraisal of the promise and limitations of complex systems theories in the study of organization. To have real value, such new ideas cannot for very long be characterized as the potential answer to almost every question. A period of testing their applicability across a spectrum of issues is needed. This will help us to determine on which problems the ideas work best, and which are best attacked with other tools.